Dziecko jako podmiot usług medycznych z punktu widzenia zgody małoletniego na interwencję medyczną - Frąckowiak, Hanna (Studia Prawnoustrojowe, 2020)
Every child has the right to special healthcare, which is guaranteed by art. 68 paragraph 3 of the Constitution, as well as art. 24 of the Convention on the Rights of the Child ratified by Poland.The child, as a dependent subject, not having sufficient knowledge and experience, does not have all the statutory rights guaranteed in the course of treatment. The legislator established the age limit with the co-decision of a minor patient regarding subjecting him to medical intervention and using medical services.The criterion of minor patient age adopted in medical law is rigid, established from above and as such often criticized by doctrine.The purpose of this study is to systematize concepts such as medical service, patient, child and to familiarize the reader with the definition of a minor patient. The author also presents individual provisions of medical law pointing out the inconsistency of the legislator in the adopted criterion of age (16 or 13 years) depending on the casuistic cases indicated in individual acts.The analyzed provisions indicate not only the inconsistency of Polish medical law but also the illogicality of certain solutions, such as granting the patient with mental disabilities but with sufficient insight, the right to express binding objection to planned medical procedures, denying this right to a minor patient under 16 years of age. The de lege ferenda conclusion is that the legislator adopts the possibility of deciding about his life and health by the criterion of the actual ability of the minor patient to consciously express a binding opinion.